Um Vice-reinado na República do pós-30: Juarez Távora, as interventorias do Norte e a Guerra de 1932 - Lopes, Raimundo Helio (2014)
This thesis deals with the trajectory of the geopolitical region then called Northern Brazil, during the Provisional Government of Getúlio Vargas (1930-1934). This region started to get organized on the immediate aftermath of Vargas’ rise to power in 1930 and, in the following years, came to be one of the most active political forces of the period. The North was formed by the then federal territory of Acre and the states of Amazonas, Pará, Maranhão, Piauí, Ceará, Rio Grande do Norte, Paraíba, Pernambuco, Alagoas, Sergipe, Bahia e Espírito Santo. At that time, the main positions of power in these states, both in politics as well as within the military, were occupied by men who called themselves northern revolutionaries. The invention and consolidation of this political identity was built upon the recognition of Juarez Távora as the great leader and representative of the regional interests within the Provisional Government. Ironically called by his political opponents the 'Vice-roy of the North', Távora lead this group during the whole period, building an important alliance between this geopolitical region and the Provisional Government. Thus, the North, its revolutionaries and its leaders, were the main supporters of Vargas and his political centralization scheme, in opposition to other lines of thought, especially the ones that favored the return of the constitutional regime. In that way, the North decisively participated in the radicalization process which led to the civil war of 1932, sending thousands of troops to the battlefields and fighting, within the region itself, the possible allies of the rebel movement lead by the state of São Paulo. As the war ended and the country returned to the constitutional regime, despite attempts to remain as a large and important political block, the region breaks apart and the old bonds that defined the identity of northern revolutionaries vanish, along with the clear leadership role of its former leader and hero, Juarez Távora.